Carbon Emission Reduction Potential and Economic Valuation of Biogas at Cengkir Gading Edufarm in Boyolali - Anggit WIJAYANGGO; Siti FATONAH; Aisyah Hadi RAMADANI (International Journal of Environmental, Sustainability, and Social Science, 2023)
Cengkir Gading Edufarm is a cattle breeding center for livestock education and manure management purposes that focuses on creating green renewable energy. The program is supported by CSR schemes carried out by PT Pertamina Patra Niaga DPPU Adi Sumarmo. The study objective is to assess the effectiveness of biogas digester construction in Cengkir Gading in reducing carbon emissions and evaluate the reduction cost in energy used. The result showed that the digester unit could help convert cattle dung waste by installing a 30 cubic sized WWTP into biogas, the amount of cow manure being accommodated as much as ± 20 kg/day (10 kg for 2 cattle). Reduction of GHG from livestock activities by 0.0162 CO2-eq Gg/year and LPG fuel by 45.377 CO2-eq Kg/year. The potential of electrical energy converted from biogas is 6.16 kWh/day, which produces a power of 0.65 kW. This digester produces 0.8 m3 biogas/day that can be converted into heat energy of 8658 kcal/day, so it potentially saved 0.19 kg/day of LPG consumption, reduced costs for purchasing LPG gas of 1,140 IDR/day or 34,200 IDR/month, it also saves the cost of paying for electricity 249,849 IDR/ month for a 900 VA.